The relation between leader’s humility and team creativity - Gonçalves, Lurdes (2018)
Purpose: Empirical studies on humility in the area of organizational studies are still scarce, as are studies of humility in leadership. This research aims to contribute to the literature by studying how the humility of leaders predicts the team's creativity through the mediating effect of psychological security and psychological capital. Design/methodology/approach: The sample includes 73 teams and their leaders, from 40 firms operating in different industries. Leaders (n = 73) described their own humility and team creativity. Team members (n = 341) described the leader’s humility, and the team’s psychological safety and psychological capital. Findings: Structural equation modelling (LISREL; maximum likelihood estimation) was used to test the hypothesized model. The findings are represented in Figure 1 (control variables not shown), and the results suggest that the leader’s humility predicts team creativity through team’s psychological safety (PsySafe) and psychological capital (PsyCap). Research limitations/implications: Main limitations are the small sample size, and the fact that it is a convenience sample, which may limit the generalization of results. One may add the need to conduct longitudinal studies, as well as have a comparison among different regions or countries. These issues are addressed in the study. Originality/value: This paper contributes to the still limited literature relating humility and leadership. For organizations, if they want to be effective in innovating, they need to understand the influence of the mechanisms that the employees are exposed to and how they influence their creativity. Knowing the positive role of humble leadership in creativity development and employee motivation is particularly interesting for leaders working in the context of creativity, as it is a way of facilitating creativity of employees.